The effect of menstrual cycle phases on speedendurance and motivation of water polo players - Schatz, P.; Shakalio, S.; Isenmann, E.; Diel, P. (Deutsche Zeitschrift für Sportmedizin, 2023)
Background: The variation of sex hormones determines menstrual cycle (MC). This variation in hormones appears to affect women's exercise performance and their recovery during a MC. Speed endurance plays a crucial role in water polo. To date, no scientific study has examined the effect of the menstrual cycle on speed endurance in water polo. Meticulous research in this field is required to maximize women's training success and recovery, as the previous methods used to design the optimal athletic training for male athletes do not necessarily translate to female ones due to their distinct physiological and hormonal profiles. › Methodology: In an experimental Pilot-Study, speed endurance of ten Bundesliga water polo players was examined. The water polo players completed 10 x 50m sprints with a series of 30 sec pause during menstrual phase, follicular phase and luteal phase. Sprint time, lactate rate, heart rate, motivation and the rate of perceived exertion of the water polo players were measured during all phases. › Outcome: A one-way repeated measures ANOVA showed that the menstrual cycle has a significant influence on the speed endurance of water polo players with a large effect size (p = .027; Cohens d ES: 0.7). In addition, the water polo players showed a significantly higher motivation in the FP than in the MP (p=.048; Cohens d ES: 0,56). › Conclusion: The water polo players appear to have a physiological, psychological and speed endurance advantage in FP than in LP and MP. In order to optimize the performance of water polo players without endangering their health, their hormone fluctuations within the cycle and their subjective feeling a MC based training should be integrated into their training periodization.